THE INFLUENCE OF EVENTS, ADVERTISING, AND SALES PROMOTIONS ON PURCHASE DECISIONS FOR SHOPEE PRODUCTS - Ardiprawiro (Asosiasi Dosen Muda Indonesia, 2026)
This study examines the influence of e-marketing strategies, specifically events, advertising, and sales promotion, on consumer purchase decisions for Shopee products. A quantitative approach was employed using primary data collected from 105 respondents through a structured questionnaire, with sampling conducted via probability sampling. Data analysis included validity, reliability, normality, multicollinearity, heteroscedasticity tests, multiple linear regression, coefficient of determination, F-test, and t-test using SPSS version 29. The results reveal that the event variable does not have a direct significant effect on purchase decisions, whereas both advertising and sales promotion exhibit a direct and positive influence. Among the three, sales promotion is the most dominant factor affecting purchase decisions. These findings underscore the importance of prioritizing advertising and promotional strategies in e-commerce marketing to enhance consumer purchasing behavior.